Inhibitory effect of phenolic acid on Ganoderma boninense enzyme as an approach on Ganoderma infection. (August 2018) - Kresnawaty, Irma; Eris, D D; Mulyatni, A S; Prakoso, H T
Abstract: Ganoderma boninense, the causal of basal stem rot (BSR) has already caused a major loss of revenue in Indonesia oil palm industry. Many methods were used to control G. boninense attacks. Phenolic compounds could be accumulated when G. boninense attacks oil palm plants and these compounds exhibit anti- Ganoderma activity. The aim of this research was to reveal the inhibitory capacity of phenolic acid against ligninolytic enzyme activity of G. boninense. Darkish-red colour around the colony of Ganoderma on lignin selective medium was observed. Extraction of crude enzymes resulted in 628.49 U/mL Laccase enzymes, 360.42 U/mL MnP enzymes, and 632.62 U/mL LiP enzyme from three replicates. We indicate that the protein concentration of the sample between 30-60 ppm according to standard series. By purified the enzyme three fractionation were obtained consist of fraction 5 which had 1254.4; 15.5; 548.39 U/mL, fraction 6 had 1394.21; 294.77; 141.58 U/mL, and fraction 7 had 196.53; 20.66 and 161.29 U/mL for the activity of laccase, MnP and LiP enzyme respectively. The addition of inhibitor resulted in the decrease of ligninolytic enzyme activity. Both syringic and caffeic acid showed a significant inhibition effect to Ganoderma.